Methylome profile of medaka eggs and sperm - Xuegeng Wang; Ramji K. Bhandari (Epigenetics)
Eggs and sperm are responsible for the continuation of generations. Following the epigenetic reprogramming of the embryo, core epigenetic information present in the sperm and eggs is transmitted to offspring somatic cells prior to the blastula stage, which specifically influences gene expression in the cells. Differences in the patterns of DNA methylation between the paternal and maternal genomes are critical to regulating allele-specific gene expression in the developing embryo, constituting the basis of genomic imprinting in mammals. While the information on allele-specific epigenetic information has been limited to mammals, it is not clearly understood whether non-mammalian vertebrate gametes possess any sex-specific allelic epigenetic information and whether somatic cells maintain the allele-specific epigenetic information, particularly DNA methylation. To determine the landscape of DNA methylation in paternal and maternal alleles in a non-mammalian vertebrate, we profiled the methylome of egg in medaka fish and compared it with our previously published medaka sperm methylome. We identified a set of gamete-specific differentially methylated regions (DMRs) in the genome- medaka eggs maintained a significantly lower global methylation profile than the sperm. Based on our sequencing depth and data, 10 DMRs were hypermethylated, and 237 DMRs were hypomethylated in the eggs compared to the sperm methylome. Somatic cells in blastula maintained some of those parental gamete-specific DNA methylation profiles. Those DMRs are associated with 70 genes, suggesting that they may have imprinted-like functions and warrant further investigation.